2002
DOI: 10.1021/ic025538f
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of a Ruthenium(II) Arene Antitumor Complex with Cysteine and Methionine

Abstract: The Ru(II) organometallic antitumor complex [(eta(6)-biphenyl)RuCl(en)][PF(6)] (1) reacts slowly with the amino acid L-cysteine (L-CysH(2)) in aqueous solution at 310 K. Reactions were followed over periods of up to 48 h using HPLC, electronic absorption spectroscopy, LC-ESI-MS, and 1D or 2D (1)H and (15)N NMR spectroscopy. Reactions at a 1 mM/2 mM (Ru/L-CysH(2)) ratio were multiphasic in acidic solutions (pH 5.1) and appeared to involve aquation as the first step. Initially, 1:1 adducts involving substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 50 publications
1
94
2
1
Order By: Relevance
“…Our previous work has shown that the interaction of [( 6 -bip)Ru(en)Cl] ϩ (2) with amino acids (38,39), peptides (40), proteins (39), and DNA bases (15) involves aquation as the first step. The chloro complexes are relatively inert.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has shown that the interaction of [( 6 -bip)Ru(en)Cl] ϩ (2) with amino acids (38,39), peptides (40), proteins (39), and DNA bases (15) involves aquation as the first step. The chloro complexes are relatively inert.…”
Section: Discussionmentioning
confidence: 99%
“…In the ideal case, such ligands would avoid the formation of aqua complexes, and thus prevent the coordination of competing biological ligands in vivo. [22,23] Thioether ligands are ideal candidates because ruthenium(II) likes binding to their soft sulfur atom. [24,25] Secondly, unlike nitrogen-based ligands, thioethers are only weakly basic in water, which might make their ruthenium complexes less sensitive to pH changes.…”
mentioning
confidence: 99%
“…Interestingly, the hydrolysis involved the displacement of the en ligand instead of the thiolate ligand, affording the di-aqua adduct 9 (Scheme 3, Figure S5). Sulfur-containing ligands such as cysteine and methionine are known to exhibit high trans effects in Pd(II) 48 , Pt(II) 49 and Ru(II) 21 coordination chemistry, labilizing metal-N bonds in the trans position.…”
Section: Reactions Of Thiolato Adduct 7 With H 2 O 2 and Gshmentioning
confidence: 99%